Hubungan Kualitas Mutu Pelayanan Keperawatan Dengan Kepuasan Pasien Rawat Inap Di RSU Mitra Sejati Medan Tahun 2024 - Ratih Widya Wati Gultom; Rian Fedriko Ginting (STIKES Columbia Asia Medan, 2025)
Quality is not easy to define but easy to feel, its form is the service of unfriendly officers, queues of visitors at the counter, long waiting times for service. This will be complained of as a service that is not in accordance with expectations, services that are of less quality so that patients feel less satisfied after getting the services provided. The formulation of the problem in this study is how is the relationship between the quality of nursing services and satisfaction of inpatients at the hospital. Mitra Sejati Medan in 2024? This research uses quantitative research using analytic survey and cross sectional approach. The population in this study were all hemodialysis outpatients, the sample of this study used accidental sampling as many as 64 people. The results of this study using the chi square statistical test, the results obtained are Responsiveness (pvalue = 0.021), Reliability (pvalue = 0.018), Assurance (pvalue = 0.030), Empathy (pvalue = 0.025), direct evidence (pvalue = 0.004), which shows that there is a relationship between The significant variables are responsiveness, reliability, assurance, empathy and direct evidence with satisfaction of inpatients at Mitra Sejati Medan hospital, and by using logistic regression test, the most dominant variable is responsiveness. This can be seen from the EXP(B) value of 4.766 times, which means that direct evidence has a relationship of 4.7 times with inpatients at Mitra Sejati Medan hospital. With suggestions to create a conducive atmosphere to improve the quality of professional health services so that patient satisfaction can be maintained as expected.